Efektivitas Pelayanan Akta Kelahiran Di Dinas Kependudukan Dan Pencatatan Sipil Kota Bitung - Rori, Angela Kelly; Sendouw, Recky; Biringan, Julien (Academy of Education Journal, 2024)
This study aims to describe and analyze the Effectiveness of Birth Certificate Services at the Population and Civil Registration Office of Bitung City, and the focus of the study is the Effectiveness and Determinant Factors of Birth Certificate Issuance Management at the Population and Civil Registration Office of Bitung City. The research method used is qualitative research. Data Collection Techniques are observation, interview, and documentation techniques. The results of the study indicate that 1) Facilities; the facilities and infrastructure for issuing Birth Certificates at the Office are still not in accordance with the Decree of the Head of the Population and Civil registration office of bitung city number 470/DKP/SK/05/2024 concerning the determination of service standards at the population and civil registration office of bitung city. Then the process or procedure for delivering birth certificates to the public is carried out directly and online. 2) Operators; the number of operators who specifically handle the issuance of birth certificates is 18 people. Then there are still obstacles in the administration of the issuance of Birth certificates experienced by operators such as network disruptions, incomplete files and people who do not want to complete the files. 3) Incentives